Molasses urea blocks as an emergency diet for sheep in the Sudan - Khidir, O.A. el; Khalafallah, A.M.; Murgos, F.I. (1989)
A ten-week trail was conducted to assess the nutritive value of molasses urea blocks (MUBs) for feeding sheep in the Sudan. Sixteen adult wethers of the Sudan Desert sheep of 51.8± 0.1 kg average liveweight were used. After a three-week preliminary period, the animals were divided according to liveweight into two equal groups which were alloted at random to either Control or Treatment. The control group was offered ad libitum a conventional diet of 60% concentrate and 40% roughage; while the treated group had free access to MUBs and weighed allowance of roughage regulated to maintain a 60% and 40% intake of the two diet fractions, respectively. The high intake of the MUBs did not induce any adverse effect on the animals. No significant (p>0.05) difference was observed between the two groups in dry matter intake (DMI). However, intake of water was significantly higher for the treated group (3 litres per kg DMI) compared with the control (2 litres per kg DMI). The control and treatment diets induced significantly different weight gains of 140 g per day and 13 g per day respectively. The recorded gain of the control wethers was due to accretion of fat depots. The results demonstrate the potential of the MUBs as a source of energy and nitrogen in sheep nutrition during periods of emergency or feed scarcity.